A reduction in temperature induces bioactive red pigment production in a psychrotolerant Penicillium sp. GEU_37 isolated from Himalayan soil. Issue 3 (March 2023) - Pandey, Neha; Jain, Rahul; Dhakar, Kusum; Sharma, Avinash; Pandey, Anita
Abstract: Filamentous fungi are being globally explored for the production of industrially important bioactive compounds including pigments. In the present study, a cold and pH tolerant fungus strain Penicillium sp (GEU_37), isolated from the soil of Indian Himalaya, is characterized for the production of natural pigments as influenced by varying temperature conditions. The fungal strain produces a higher sporulation, exudation, and red diffusible pigment in Potato Dextrose (PD) at 15 °C as compared to 25 °C. In PD broth, a yellow pigment was observed at 25 °C. While measuring the effect of temperature and pH on red pigment production by GEU_37, 15 °C and pH 5, respectively, were observed to be the optimum conditions. Similarly, the effect of exogenous carbon and nitrogen sources and mineral salts on pigment production by GEU_37 was assessed in PD broth. However, no significant enhancement in pigmentation was observed. Chloroform extracted pigment was separated using thin layer chromatography (TLC) and column chromatography. The two separated fractions i.e., fractions I and II with Rf values 0.82 and 0.73, exhibited maximum light absorption, λ max, at 360 nm and 510 nm, respectively. Characterization of pigments using GC–MS showed the presence of the compounds such as phenol, 2, 4-bis (1, 1-dimethylethyl) and eicosene from fraction I and derivatives of coumarine, friedooleanan, and stigmasterole in fraction II. However, LC-MS analysis detected the presence of derivatives of compound carotenoids from fraction II as well as derivative of chromenone and hydroxyquinoline as major compounds from both the fractions along with other numerous important bioactive compounds. The production of such bioactive pigments under low temperature conditions suggest their strategic role in ecological resilience by the fungal strain and may have biotechnological applications. Graphical abstract: Image 1